Coolie Tajoh Festival, Trinidad, B.W.I. - (:unkn) unknown (My University, 2011)
The postcard shows crowds on the street following a Tadjah or miniature temple which is an integral part of the Hosay celebrations in Trinidad. Postcard numbered 12 50051.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Festivals--Trinidad and Tobago; East Indians--Trinidad and Tobago; Muslims--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hosay